Suppressed hysteresis and enhanced performance of triple cation perovskite solar cell with chlorine incorporation. Issue 48 (4th December 2018) - Li, Lingfeng; Zhou, Peng; Li, Jing; Mo, Yanping; Huang, Wenchao; Xiao, Junyan; Li, Wei; Ku, Zhiliang; Zhong, Jie; Peng, Yong; Cheng, Yi-Bing; Huang, Fuzhi
Abstract : Cl-Incorporated triple-cation perovskite, as a novel absorber, has been developed to suppress hysteresis and enhance photoelectric performance. Abstract : Cs/FA(CH(NH2 )2 + )/MA(CH3 NH3 + ) triple cation composition engineering is considered as an effective strategy to achieve high performance devices due to the excellent bandgap, uniform film and highly thermal stability. However, hysteresis, as a common phenomenon in perovskite solar cells (PSCs), of the triple-cation perovskite based PSCs has become a complex issue to be solved on the road to the commercialization of PSCs. The introduction of Cs into small perovskite grains resulted in more grain boundaries for ions accumulation. Herein, we demonstrate a unique method to suppress J – V hysteresis and enhance the photoelectric performance via Cl doping into a CsFAMA precursor. We found that the grain size, perovskite crystallinity, and charge carrier lifetime significantly improved with the Cl incorporation. By optimizing the molar ratio of MABr and PbCl2, we achieved the optimal Cl-doped concentration in the perovskite film. 19.14% efficiency for a small area cell and 15.11% efficiency for a 5 × 5 cm 2 large area mini-module were achieved based on the mesoporous structured devices. These results suggest that Cl-incorporated triple-cation perovskite (labeled CsFAMACl x ) is an attractive absorber for producing efficient large area PSCs.